Introducing a Task Management Tool into the Operation of a Management Consulting Firm - Tarjáni, Ariella Janka; Kalló, Noémi; Pataki, Béla (International Journal of Engineering and Management Sciences, 2021)
Lean and agile methods are now widely used in various fields. Seeing their success, management consultancy firms also want to take advantage of using them. In this case study, the company selects the appropriate task management tool for their operation, the kanban board, and implements it. The implementation process is supported by quantitative analysis. In order to track the introduction progress of the kanban board, a key performance index is defined: the board activity, which is the number of operations performed on the board in a given time period. Based on the evaluation of over 26 weeks’ data, board activity proved to be an appropriate indicator of the kanban board’s reception, operation, and stability. The individual indicators examined, however, were not found to be suitable for performance appraisal.